Evaluating the microbial pattern of periprosthetic joint infections of the hip and knee. Issue 11 (November 2018) - Rosteius, Thomas; Jansen, Oliver; Fehmer, Tobias; Baecker, Hinnerk; Citak, Mustafa; Schildhauer, Thomas Armin; Geßmann, Jan
Abstract : Purpose. : Periprosthetic joint infection (PJI) is a devastating complication that leads to enormous economic and health care complaints from affected patients. The aim of this study is to identify the causative pathogens responsible for PJI, evaluate temporal trends concerning the pathogen pattern and identify potential risk factors for PJI. Methodology. : This was a retrospective study analysing a total of 937 patients suffering PJI of the hip or knee joint between 2003 and 2011. Results. : In total, 394 patients (42.0 %) with total knee arthroplasty (TKA), 477 patients (50.9 %) with total hip arthroplasty (THA) and 64 patients (6.8 %) receiving a dual‐head prosthesis had to be hospitalised due to PJI. In two cases (0.2 %), a simultaneous infection of TKA and THA occurred. The mean age of the study cohort was 70.85±11.68 years. The mean body mass index (BMI) was 28.53±5.7. According to the Charlson comorbidity index, 2.99 % of the patients were classified as severity Grade 1, 13.98 % Grade 2, 40.02 % Grade 3 and 43.0 % Grade 4. Staphylococcus aureus (MSSA), methicillin‐resistant Staphylococcus epidermidis (MRSE), methicillin‐resistant Staphylococcus aureus (MRSA), coagulase‐negative Staphylococcus (CoNS), Streptococcus, and Enterococcus were the pathogens mainly responsible. An increase in high‐resistance pathogens, such as MRSE, extended‐spectrum beta‐lactamase bacteria (ESBL), ampicillin‐resistant Enterococcus, Acinetobacter spp. and vancomycin‐resistant Enterococcus (VRE), was found during the study period. Only MRSA showed a declining tendency in a regression model. Conclusion. : Patients suffering PJI present a certain risk profile with many comorbidities, e.g. high age and obesity. The observed microbiological pattern demonstrates the rise of high‐resistance pathogens.